PENGARUH KOMPENSASI TERHADAP MOTIVASI KINERJA KARYAWAN PADA PT. MNCLEASING PALEMBANG - Kemas Adipati (Jurnal Ilmiah Ekonomi Global Masa Kini)
In this study, the authors take the title "Influence of Employee Compensation Motivation.MNC Leasing  company palembang". This research was conducted by the author is to determine how much influence the compensation on employee motivation MNC Leasing  company Palembang. This research uses quantitative data analysis techniques. The research data was obtained from the respondents (questionnaire) in company MNC Leasing  , in this case the primary data that is diteknik pemgambilan the data obtained from the MNC Leasing  company. The statistical analysis used in this research is regression analysis and hypothesis testing using the program SPSS 16. The results of this study indicate that there are significant compensation to big motivation that can be seen from the results of the variable coefficients x of 56.4 percent, the presence of a considerable influence on employee motivation in the MNC Leasing  company will certainly be able to improve progress for the company, can also be the prosperity of employees working with bonuses for their hard work on the profits earned by the company as compensation makes employee motivation increases and would make the company's productivity increased well.Keywords : Compensation , Motivation Productivity, Employee.